KECERNAAN RANSUM PADA KELINCI BETINA LOKAL YANG DIBERI RANSUM MENGGUNAKAN AMPAS TAHU TERFERMENTASI DENGAN ARAS BERBEDA - Nuriyasa I M.; A. W. Puger (Fakultas Peternakan Universitas Udayana, 2019)
This study aims to determine the digestibility of local female rabbit fed diet containing different levels offermented tofu waste. The study used a randomized block design (RBD), with five treatments and five blocks.The treatment was rabbits fed rations without using tofu waste or control fed (R0), rabbit fed rations containing10% tofu waste (R1), rabbit fed containing 15% tofu waste (R2), rabbit fed rations containing 10% fermented tofuwaste (R3) and rabbit fed rations containing 15% fermented tofu waste (R4). Variables observed were dry matterdigestibility, protein digestibility and efficiency of changes GE to DE. The results showed that rabbits fed ration R3and R4 caused dry matter digestibility, protein digestibility and efficiency of changes GE to DE were higher thantreatments R2, R1 and R0. It can be concluded that diets containing 10% up to 15% fermented tofu waste in rabbitrations can increase the digestibility of rations for local female rabbits.